A dysregulated acetyl/SUMO switch of FXR promotes hepatic inflammation in obesity. (25th November 2014) - Kim, Dong‐Hyun; Xiao, Zhen; Kwon, Sanghoon; Sun, Xiaoxiao; Ryerson, Daniel; Tkac, David; Ma, Ping; Wu, Shwu‐Yuan; Chiang, Cheng‐Ming; Zhou, Edward; Xu, H Eric; Palvimo, Jorma J; et al.
<x xml:space="preserve">Abstract</x> Elevated acetylation of the mouse nuclear Farnesoid X receptor (FXR) in obesity inhibits its SUMOylation, which promotes hepatic inflammation and metabolic dysfunction in vivo.<boxed-text content-type="graphic" id="embj201489527-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text>